2021
DOI: 10.1111/crj.13453
|View full text |Cite
|
Sign up to set email alerts
|

The role of ventilatory support for long‐term outcomes after critical infection with COVID‐19: A prospective cohort study

Abstract: Objectives The full range of long‐term health consequences in intensive care unit (ICU) survivors with COVID‐19 is unclear. This study aims to investigate the role of ventilatory support for long‐term pulmonary impairment in critically ill patients and further to identify risk factors for prolonged radiological recovery. Methods A prospective observational study from a single general hospital, including all with COVID‐19 admitted to ICU between March and August 2020, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A detailed description of this data collection can be found in other publications 7 8. Data on demographic and clinical details were retrieved from medical charts regarding age (≤50, 50–65, >65 years), sex (male/female), body mass index (BMI), smoking habits (ever/never), comorbidities (ie, diabetes, hypertension/cardiovascular disease, chronic lung disease) Simplified Acute Physiological Score III (a scoring system used to predict mortality risk in the ICU), where a higher score indicates a higher mortality risk,14 corticosteroid treatment (yes/no), respiratory support (invasive vs HFNO/NIV) and ICU length of stay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of this data collection can be found in other publications 7 8. Data on demographic and clinical details were retrieved from medical charts regarding age (≤50, 50–65, >65 years), sex (male/female), body mass index (BMI), smoking habits (ever/never), comorbidities (ie, diabetes, hypertension/cardiovascular disease, chronic lung disease) Simplified Acute Physiological Score III (a scoring system used to predict mortality risk in the ICU), where a higher score indicates a higher mortality risk,14 corticosteroid treatment (yes/no), respiratory support (invasive vs HFNO/NIV) and ICU length of stay.…”
Section: Methodsmentioning
confidence: 99%
“…The majority survived the acute episode of a critical illness but were confronted with physical and psychological sequelae after discharge from hospital which prolonged recovery 3. Approximately 35%–80% of the survivors experienced persistent symptoms of fatigue, dyspnoea, joint pain, sleep disorders, and loss of memory and concentration lasting beyond 4 weeks after a moderate to severe acute infection, which is referred to as ‘postacute COVID-19 syndrome’4–6 Long-lasting respiratory complications as well as other functional deficits which may cause substantial morbidity have been reported among intensive care unit (ICU) survivors in the first year after hospital discharge 7–10. Furthermore, a high number of residual abnormalities on chest CT scan have been found several months after discharge from hospital, and acute respiratory distress syndrome has been associated with more severe radiological findings 11.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary function was measured in 11 studies 13,48,49,51,56,66,71,74,75,77,79 , of these 7 were on classical ARDS with 723 patients and 6 studies on SARS-CoV-2 ARDS with 651 patients. Studies mainly reported Forced Vital Capacity (FVC) and Forced Expiratory Volume (FEV 1 ) over 12 months.…”
Section: Pulmonary Functionmentioning
confidence: 99%
“…One study comparing critical COVID-19 patients who underwent non-invasive versus invasive mechanical ventilation showed a lower TLC for patients with invasive ventilation 6 months after discharge. [19] Further studies reporting on long-term outcomes of critical patients treated with non-invasive ventilation or high-flow nasal oxygen compared with invasive mechanical ventilation could shed more light on the magnitude of this damage.…”
Section: Discussionmentioning
confidence: 99%